2022
DOI: 10.3390/antibiotics11020215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Exposure to Chlorine Dioxide on the Susceptibility of Fecal Coliforms to Antibiotics

Abstract: Adaptive exposure to sub-lethal concentrations of sanitizers was previously reported to offer cross-protection to bacteria against antibiotics. This study was undertaken to determine whether the pre-exposure of fecal coliforms to suboptimal concentrations of a chemical sanitizer, chlorine dioxide (ClO2), alters their susceptibility to certain antibiotics. Fecal coliforms isolated from fresh fruit packing facilities (n = 12) were adapted in ½ or ¼ of the manufacturer-recommended concentration of ClO2. The susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The exact mechanism of action of ClO 2 remains unclear, with some studies suggesting DNA damage and others suggesting protein denaturation by oxidation [ 43 ]. Previous studies have suggested that preexposure of S. Typhimurium to ClO 2 increased resistance to STR, erythromycin, rifampicin, and CHL [ 44 ]. NaClO was the disinfectant that had the lowest effect on antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism of action of ClO 2 remains unclear, with some studies suggesting DNA damage and others suggesting protein denaturation by oxidation [ 43 ]. Previous studies have suggested that preexposure of S. Typhimurium to ClO 2 increased resistance to STR, erythromycin, rifampicin, and CHL [ 44 ]. NaClO was the disinfectant that had the lowest effect on antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%